The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.wavemoti.2019.102402
|View full text |Cite
|
Sign up to set email alerts
|

Mono-scale and multi-scale formulations of gradient-enriched dynamic piezomagnetics

Abstract: This is a repository copy of Mono-scale and multi-scale formulations of gradient-enriched dynamic piezomagnetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…It can be seen that the wave fronts of all four fields becomes less and less steep as time progresses. This is an indication that the harmonic components of higher frequency travel with lower velocity, and confirms that the model is dispersive-see [44] and Section 6.1 above. The micro-scale fields are more oscillatory than the associated macro-scale fields, which can be understood from the equivalence with homogenisation as explained in Section 2.…”
Section: Wave Dispersionsupporting
confidence: 73%
See 3 more Smart Citations
“…It can be seen that the wave fronts of all four fields becomes less and less steep as time progresses. This is an indication that the harmonic components of higher frequency travel with lower velocity, and confirms that the model is dispersive-see [44] and Section 6.1 above. The micro-scale fields are more oscillatory than the associated macro-scale fields, which can be understood from the equivalence with homogenisation as explained in Section 2.…”
Section: Wave Dispersionsupporting
confidence: 73%
“…Next, the effect of the various length scales ℓ 1 , ℓ 3 and ℓ 4 on the dispersive properties of the material is investigated in more detail. In [44] and in Section 6.1, we demonstrated that the ratio ℓ 4 /ℓ 1 is the dominant parameter in this context, with higher wave numbers travelling slower for increased values of ℓ 4 /ℓ 1 . In Figure 6 we have plotted the results of micro-scale and macro-scale strain for two ratios of ℓ 4 /ℓ 1 .…”
Section: Wave Dispersionmentioning
confidence: 58%
See 2 more Smart Citations